The specific heat of matter at low temperatures - Tari, A. (Ahmet) (Imperial College Press ; Distributed by World Scientific Pub. Co., 2003)
Recent discoveries of new materials and improvements in calorimetric techniques have given new impetus to the subject of specific heat. Nevertheless, there is a serious lack of literature on the subject. This invaluable book, which goes some way towards remedying that, is concerned mainly with the specific heat of matter at ordinary temperatures. It discusses the principles that underlie the theory of specific heat and considers a number of theoretical models in some detail. The subject matter ranges from traditional materials to those recently discovered - heavy fermion compounds, high temperature superconductors, spin glasses and so on - and includes a large number of figures, tables and references. The book will be particularly useful for advanced undergraduate and postgraduate students as well as academics and researchers.